Effectiveness of 3% arbutin cream in the treatment of epidermal melasma (Journal of Fatima Jinnah Medical University, 2020)
Background: Melasma is a common acquired, circumscribed hypermelanosis of sun-exposed areas. Multiple treatment options are available for melasma but they require a long time to yield effective results. Arbutin has shown promising results in the treatment of melasma. The objective of this study was to determine the effectiveness of 3% arbutin cream in the treatment of epidermal melasma.Patients and Methods: It was an interventional study conducted at the Department of Dermatology, Sir Ganga Ram Hospital, Lahore from 1st September, 2011 to 29th February, 2012. After approval from the Hospital Ethical Committee a total of 120 patients with epidermal melasma (diagnosed on Wood’s Lamp Examination), were enrolled in the study. All the patients were advised to apply 3% arbutin cream twice daily for 12 weeks. They were advised to do follow up visits every 2 weeks with a final visit 2 week after completion of treatment. Melasma Area Severity Index (MASI)1 score was calculated at the baseline and 2 weeks after completion of treatment period. Efficacy was measured by the decrease in MASI score (>50%). All the information was collected on a specially designed proforma. Photographs were taken at the start and end of study period.Results: There were 7 (5.8%) male patients and 113 (94.2%) female patients in the study. The male to female ratio was 1:16.4. The mean age of patients was 33.93±6.1. In this study, 65 patients (54.16%) showed improvement in terms of >50% reduction in MASI score at 2 weeks follow up visit after the completion of treatment.Conclusion: Use of arbutin 3% cream is an effective treatment modality in patients of epidermal melasma.
Keywords: Efficacy; melasma; arbutin